Secondary Colour Terms in the English and Ukrainian Fiction - I A Gerasimenko (RUDN Journal of Language Studies, Semiotics and Semantics, 2015)
The article presents the comparative analysis of secondary colour terms in English and Ukrainian fiction. The research deals with structural and semantic peculiars of the given units in two languages. The author analyzes the ways of building, enrichment sources, contextual meaning and the functioning of secondary colour terms in English and Ukrainian. The topicality of the article is determined by the tendency of modern linguistics to contrastive study of language units. The results of our analysis testify to the fact that in spite of the belonging of studied secondary colour terms to different language groups (Germanic and Slavonic) and morphological types (analytic and synthetic) there are a lot of common features in functioning of the given units as for their structure, semantic and contextual environment.